Strategi Keberlanjutan dan Transformasi Digital di Industri Fast Fashion: Studi Kasus Uniqlo - Cloudia, Fabella (AKADEMIK: Jurnal Mahasiswa Humanis, 2025)
The fast fashion industry has grown rapidly by providing trendy and affordable clothing, but it has led to negative environmental impacts, such as increased carbon emissions and textile waste. UNIQLO, as one of the key players in this industry, applies the Net Positive principle to create a positive impact that exceeds its negative effects. By leveraging digital transformation, UNIQLO enhances operational efficiency and transparency in its business. This article discusses UNIQLO's strategy of integrating the Net Positive concept with digital technology. The analysis results show that through supply chain tracking, AI-based inventory management, and consumer education programs, UNIQLO has successfully reduced textile waste, decreased carbon emissions, and increased loyalty among environmentally-conscious consumers. These strategic steps not only help UNIQLO reduce its environmental impact but also strengthen its competitiveness in the global fast fashion market. UNIQLO's approach serves as a real example for other companies in the industry that aim to adopt a sustainable business model, especially in the digital era, which demands innovation and environmental responsibility.